If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+19y=45+y
We move all terms to the left:
-9+19y-(45+y)=0
We add all the numbers together, and all the variables
19y-(y+45)-9=0
We get rid of parentheses
19y-y-45-9=0
We add all the numbers together, and all the variables
18y-54=0
We move all terms containing y to the left, all other terms to the right
18y=54
y=54/18
y=3
| -8(-7x-4)=-14 | | 10z=10z+7 | | 3x+23=(48)+(2x+5) | | (12x-3)=(7x+37) | | -32.4+x=12 | | x2=10x−24 | | -(6x+7)=17 | | -7m+4=-9-7m | | 0.36x=1 | | (4x)^2=256 | | 8s=9+7s | | 15+19y–24=45+y | | 5x-7+147=180 | | (4x)=256 | | 51=15x-6 | | -2g=-9g+7g | | 6+1/x=14/2x | | -24=-2k+8k | | r-4=2r= | | 8/x=142 | | 3t+19+36=76+t+5 | | -10t+t=-9t | | -8/10x=-5 | | 9b=8+10b | | 1/7+x=12/14 | | 11=2x+3= | | -14+4+2a-3a=a-4 | | 3a-(-8a)=3a | | 2^x+45=121 | | 5x+44x=12 | | -5x-1=2x=4 | | .2x-4/9=32/9 |